IMPACT OF THE SHADOW ECONOMY ON FOOD SECURITY IN UKRAINE - FEDUN, Igor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The impact of the shadow economy on Ukraine’s food security is a multifaceted and complex issue. The purpose of this study is to analyze the relationship between the shadow economy and the state of food security in Ukraine. The analysis identified the main forms of the shadow economy in the agricultural sector: land transactions, unauthorized sales of products, tax evasion, gray import/export of agricultural products, and illegal use of labor. Key areas of the shadow economy’s impact on Ukraine’s food security were identified: reduced efficiency of state regulation of the agribusiness, financial instability of the agricultural sector, deterioration of food statistics, violation of quality and safety standards. General ways to reduce shadowing in the agricultural sector were formulated: regarding land transactions (strengthening the land cadastre, mandatory registration of all contracts, fiscal control and motivation, transparency of the land market, increased responsibility, educational campaigns for unit owners); on unauthorized sales of products (strengthening state control, stimulating legal business, developing sales infrastructure, education and information policy, involving the public and the media, improving legislation); on tax evasion (digitalization and automation of accounting, reform of the taxation system, expanding access to financing only for "white" farms, strengthening control and responsibility, increasing the level of legal awareness); on gray import/export of agricultural products (strengthening customs control, digitalization of the agricultural sector, improving the VAT system and tax administration, developing the institute of agricultural exchanges, reform of the State Service for Food and Consumer Protection and certification, international cooperation); on illegal use of labor (legislative initiatives and control; educational and information campaigns; economic incentives; digital solutions; cooperation with public organizations and trade unions). The use of innovations as the main tool for combating the shadow economy in the agricultural sector, including in the context of sustainable development goals, is highlighted and justified. The main challenges to the implementation of innovations are identified: resistance from corrupt officials, insufficient level of digital literacy, problems with financing and infrastructure, the need for regulatory support.